Identifying potentially valuable flavour fractions from South African botanical extracts using LC Taste as a rapid screening method - Van der Merwe, Emma (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScFoodSc)--Stellenbosch University, 2020.